The Social Logic of Nursing Communication and Team Processes in Centralized and Decentralized Work Spaces. Issue 14 (6th December 2019) - Real, Kevin; Santiago, Joshua; Fay, Lindsey; Isaacs, Kathy; Carll-White, Allison
ABSTRACT: This pre–post multi-method study explored how nurses made sense of changes in nurse station design and how they characterized communication processes within a hospital unit before and after it moved from an existing hospital into a newly designed trauma-1 level hospital. Quantitative observations (116 h) of real-time communication were gathered in both hospitals. Additionally, 41 nursing staff (nurses, nursing care technicians, nurse managers) participated in a qualitative study. Three months before moving, four focus groups were conducted with 16 nursing professionals working in traditional centralized nurse station units. One year later, four additional focus groups were conducted with 25 nursing staff in new decentralized units. The observational data resulted in two key findings: first, nursing staff participated in about 70 percent of interactions with nurses, techs, doctors, and families. Second, nursing communication decreased in decentralized units. In-depth qualitative analysis revealed that nursing communication was more frequent, relational and supportive in centralized spaces while distinguished by fragmentation and information exchange in decentralized units. Drawing upon theories of supportive design and healthcare systems, these findings illustrate how nurses in centralized units characterized communication as proximity, teamwork and relationships. Nurses in decentralized units described communication in terms of distance, fragmentation, and information exchange. Implications of this study suggest that centralized spaces may facilitate nursing communication while decentralized units are supportive of proximity to patients. Exploring how communication and design together constitute the logic of healthcare delivery contributes to our understanding of how communication processes comprise the social organization of nursing care.